EFFECT OF CHRONIC EXPOSURE OF SPECKLED PRAWN, METAPENAEUS MONOCEROS (FABRICIUS) TO NAPHTHALENE - Deshmukh, Nandini V; Masurekar, Vasant B (Indian Journal of Fisheries, 2011)
Naphthalene, the most toxic constituent of petroleum hydrocarbon was selected as a pollutant to study the effects on survival of speckled prawn, Metapenaeus monoceros which is one of the commercially important species of edible prawns. The prawns were exposed to different concentrations of naphthalene by employing static bioassay procedure for 1 to 8 week period. Adverse effects on survival in M. monoceros were found to be directly related to the concentration of naphthalene used. Mortality rates thus obtained served as index of the effects of chronic exposure to different naphthalene concentrations on the survival of the animals.